(untitled) (Malaysian Journal of Learning and Instruction, 2022)
Purpose – Previous studies have documented the positive effect of problem-based learning (PBL) on learners, especially in the medical discipline. However, such effect on learners in a specific course of Systems Analysis and Design (SAD) and how the PBL implementation in this course could contribute to meaningful learning are still under-researched. Therefore, this study aims to investigate how a PBL approach could be used in creating meaningful learning among the students of SAD and its effect on their skills. The focus is on how meaningful learning could be achieved through the integration of active learning with fun activities along with the use of technology (Active Fun Technology (AFT) elements) to nurture the students’ knowledge and enhance their soft skills. Methodology – The qualitative approach was adopted as a means to understand how PBL integrated with AFT elements could create meaningful learning experiences and its impacts on skills development. 108 self-reflections were received from the students. A thematic analysis was used to analyse data from the students’ self-reflection. Findings – Meaningful learning criteria and AFT elements were embedded during the process to create meaningful learning experiences. The finding of this study highlighted that PBL activities with the integration of AFT elements could be used to create meaningful learning. The study showed that the PBL implementation successfully created a meaningful learning experience and developed related skills during the learning process. In this regard, two major themes emerged from the thematic analysis, namely soft skills (social skills [with subthemes of friendship and sharing, accept others’ ideas], teamwork, communication, critical thinking, and problem-solving), and technical skills. Significance – The significance of the study was its suggestion of integrating AFT elements during the design and implementation of PBL activities. This is particularly important for educators who teach highly theoretical subjects and use PBL as their teaching approach and strategy to ensure engagement in stimulating students’ interests to learn the subject.